Pengembangan LKPD Berbasis Problem Based Learning Bermuatan Etnosains Pada Materi Sistem Koloid - Lia, Zulfa Aulia Hasni; Junaidi, Eka; Hadisaputra, Saprizal (Chemistry Education Practice, 2024)
This study aims to determine the characteristics, level of feasibility, and practicality of Student Worksheets (LKPD) based on ethnoscience-based problem-based learning based on the main material of colloidal systems. This study is a type of research and development that adopts the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation) developed by Dick and Carry in 1990. The location of this research was conducted at SMAN 1 Kediri. The level of feasibility of LKPD was measured through an expert validation sheet, and several aspects of the assessment were assessed by 3 validators using the Aiken V index. There were 2 validation questionnaires used in measuring the feasibility of LKPD, namely physical validation and content validation of LKPD. The results showed that the physical validity value of LKPD was 0.83, which is a very valid category, and the content validity value of LKPD is 0.82, which is a very valid category. The level of practicality of LKPD was measured through a response questionnaire filled out by 48 students of class XI MS SMAN 1 Kediri. The results of the analysis of student responses show that the developed LKPD is said to be very practical because it has a practicality percentage of 87%. Based on these results, it can be concluded that the developed LKPD is feasible and practical and can be used in learning colloidal systems.